Using GIS and remote sensing to monitor industrial impacts to archaeological sites in the Athabasca Oil Sands of Alberta - Wadsworth, William T. D.; Dersch, Ave; Woywitka, Robin; Supernant, Kisha (My University, 2021)
The Athabasca Oil Sands (AOS) region of Alberta has one of the densest accumulations of known archaeological sites, and possibly the most archaeological sites at risk, in the country. Expanding industrial development has been a characteristic of this region for decades, and as a result, abundant archaeological work has been done and regulatory requirements put in place to mitigate site disturbance. Until recently, there has been little quantitative evidence to assess human impact on archaeological resources in the region. The goal of this paper is to raise awareness of the critical need to incorporate new archaeological remote sensing strategies to improve site monitoring approaches. We present methods and results from our GIS-based analysis that seeks to locate and partially characterize impacted sites. We argue that combining publicly accessible remote sensing products with geospatial archaeological site information allows for better documenting and monitoring of industry impacts in the AOS. We show that 43% of all sites sampled (n=1943) are disturbed. Of these sites, 160 were potentially affected by Historical Resources Act non-compliant impacts (including five HRV 1 sites). We contextualize our results within current systemic challenges and we recommend the incorporation of community monitoring programs to ground-truth similar GIS analyses and increase our ability to effectively monitor industrial impacts to archaeological sites.
Keywords: Athabasca Oil Sands; monitoring; disturbance; GIS; remote sensing; site boundaries; northern Alberta; Indigenous archaeology; impact; Boreal Forest